UJI AKTIVITAS ANTIBAKTERI DAN ANTIBIOFILM EKSTRAK ETANOL DAUN MATOA (Pometia pinnata J. R & G. Forst) TERHADAP BAKTERI Pseudomonas aeruginosa - Putri, Seprina; Indrayati, Ana; Wulandari, Destik (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
Pseudomonas aeruginosa is a multi-drug resistant (MDR) pathogen known for its ability to form biofilms, making it difficult to eliminate. This study aimed to evaluate the effectiveness of ethanol extract from matoa leaves (Pometia pinnata) as an antibacterial and antibiofilm agent against P. aeruginosa. The antibiofilm activity was assessed using the Crystal Violet (CV) method with absorbance measured at a wavelength of 595 nm. The percentage of biofilm inhibition was used to determine the ICâ‚…â‚€ value. Phytochemical analysis revealed that the ethanol extract of matoa leaves contains alkaloids, flavonoids, tannins, and triterpenoids, which contribute to its antibacterial and antibiofilm activity. The minimum inhibitory concentration (MIC) was determined to be 25 mg/mL. Inhibition zone tests showed that the ethanol extract at concentrations of 75, 50, and 25 mg/mL produced inhibition zones of 13.33 mm, 12.16 mm, and 10.8 mm, respectively, while the positive control, ciprofloxacin 5 µg, produced an inhibition zone of 35.67 mm. The percentages of biofilm inhibition were 21.51% (50 mg/mL) and 12.34% (25 mg/mL), with an average ICâ‚…â‚€ value of 27.43 mg/mL. These findings suggest that the ethanol extract of matoa leaves has potential as an antibacterial and antibiofilm agent against P. aeruginosa. Keywords: Pseudomonas aeruginosa, Antibacterial, Antibiofilm, Matoa leaves